Fortaleza Cidade do Design da Unesco: avaliação de uma política cultural a partir da classe criativa dos designers - Sousa, Valdemice Costa de (2025)
This research assesses how the UNESCO Creative City of Design designation of Fortaleza contributes to the local development, with an emphasis on the participation of designers in the actions of this public policy. The research is part of the field of public policy evaluation and uses the theoretical-methodological perspective of in-depth evaluation, which addresses four dimensions: content analysis, context analysis, institutional trajectory of the policy, and temporal and territorial spectrum. The main objective of this work is to evaluate the actions resulting from the designation of Fortaleza from the point of view of the creative class of local designers. It also intended to investigate whether these professionals participated effectively in the initiatives of this policy and whether they promoted their protagonism in the labor market, both in the public and private sectors. The study also examines the concept of creative cities, inclusive practices and the social participation of designers, as well as the connection with the creative economy in the context of UNESCO's Creative Cities of Design. The methodological approach of the investigation adopts a bibliographic survey of existing documents related to the granting and maintenance of the seal, in order to support the analytical dimensions of the in-depth evaluation. The analysis of documents and semi- structured interviews with stakeholders who have or have had some direct or indirect participation in the actions of the seal revealed that this policy only partially achieved its originally intended results, and with relatively significant impacts only from actions arising from specific projects/initiatives, in the context of the seal, especially for the creative class of professional designers based in Fortaleza-CE and, consequently, for the development of the city.